2008
DOI: 10.3171/foc/2008/24/6/e10
|View full text |Cite
|
Sign up to set email alerts
|

Operative intracranial infection following craniotomy

Abstract: Object Postoperative infection after cranial surgery is a serious complication that requires immediate recognition and treatment. In certain cases such as postoperative meningitis, the patient can be treated with antibiotics only. In cases that involve a bone flap infection, subdural empyema, or cerebral abscess, however, reoperation is often needed. There has been significant disagreement regarding the incidence of postoperative central nervous system (CNS) infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
104
3
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(122 citation statements)
references
References 22 publications
8
104
3
7
Order By: Relevance
“…Some studies, which discuss complications after craniotomy surgery without harvesting scalp vessels, suggest that wound infection occurs in about 5% of all patients (1%-11%). 6,7,10,20,25 In the report by Katsuta et al, 10 17.6% of patients who underwent cerebral revascularization surgery developed cutaneous necrosis without the appearance of infection. Based on these reports, wound complications after craniotomy surgery without harvesting scalp vessels are estimated to occur in 10%-15% of all patients.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies, which discuss complications after craniotomy surgery without harvesting scalp vessels, suggest that wound infection occurs in about 5% of all patients (1%-11%). 6,7,10,20,25 In the report by Katsuta et al, 10 17.6% of patients who underwent cerebral revascularization surgery developed cutaneous necrosis without the appearance of infection. Based on these reports, wound complications after craniotomy surgery without harvesting scalp vessels are estimated to occur in 10%-15% of all patients.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have reported S.aureous as the most frequent organism, a lot of results related to nosocomial and post-surgical meningitis [2,10,18,19] . Some other studies have demonstrated Streptococcus pneumonia is the most common pathogen in post-surgical meningitis [6] , however the incidence of S. pneumonia observed more in the children [12] .…”
Section: Discussionmentioning
confidence: 96%
“…4,16,32,33,36,37,42,43,45 Neurosurgery studies indicate that increased operative time is a significant risk factor for infections and cranial nerve injury following craniotomy and carotid endarterectomy, respectively. 11,13,22,25 Thus, the differences in operative time between the two cohorts may explain some of the increase in complication rates with resident involvement prior to baseline adjustment.…”
Section: Multivariate Analyses and Confounding Factorsmentioning
confidence: 99%